2009 IEEE International Symposium on Parallel &Amp; Distributed Processing 2009
DOI: 10.1109/ipdps.2009.5161095
|View full text |Cite
|
Sign up to set email alerts
|

The impact of network noise at large-scale communication performance

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…We attribute this variation to interference with other applications (cf. network noise in [12]). However, using the statistical methods explained in Section III-A, we are able to provide the relative variance for each of the parameters in brackets.…”
Section: Performance On Various Architecturesmentioning
confidence: 99%
“…We attribute this variation to interference with other applications (cf. network noise in [12]). However, using the statistical methods explained in Section III-A, we are able to provide the relative variance for each of the parameters in brackets.…”
Section: Performance On Various Architecturesmentioning
confidence: 99%
“…More information about ORCS and the source-code are available in [8] and at http://www.unixer.de/research/orcs/. Based on ORCS simulation results, we analyzed the impact of Network Noise (due to background network congestion) on collective algorithms and applications [3].…”
Section: Activitiesmentioning
confidence: 99%
“…The research completed in this period has improved understanding of when such noise will have a significant impact. Specifically, it was demonstrated that not just noise on the nodes, but also noise on the network between nodes can have a significant impact on computation time [3]. It was also demonstrated that noise patterns matter more than noise intensity: very regular noise can cause less disruption than lighter (on average) but less regular noise [9].…”
mentioning
confidence: 99%
“…This is also coupled with the availability of advanced network hardware which is capable for offloading communication operations. Such offloaded collective communication is beneficial to systems that can be prone to OS noise [3], [8]. Finally, applications stand to gain significantly from nonblocking collectives by overlapping computation and communication, without having to resort to re-programming collectives using non-blocking point-to-point operations, as evidenced in High-performance Linpack benchmark (HPL) [9].…”
Section: A Mpi Collective Operations: Past Present and Futurementioning
confidence: 99%
“…Thus, enabling overlap of computation and communication. In addition, non-blocking collectives can also help mitigate OS-noise issues, that can often impact performance at scale [3], [8].…”
Section: Introductionmentioning
confidence: 99%